Disturbed flow regulates protein disulfide isomerase A1 expression via microRNA-204 - Tanaka, Leonardo Y.; Kumar, Sandeep; Gutierre, Lucas F.; Magnun, Celso; Kajihara, Daniela; Kang, Dong-Won; Laurindo, Francisco R. M.; Jo, Hanjoong (Frontiers in Physiology, 2024)
Redox processes can modulate vascular pathophysiology. The endoplasmic reticulum redox chaperone protein disulfide isomerase-A1 (PDIA1) is overexpressed during vascular proliferative diseases, regulating thrombus formation, endoplasmic reticulum stress adaptation and structural remodeling. However, both protective and deleterious vascular effects have been reported for PDIA1, depending on cell type and underlying vascular condition. Further understanding of this question is hampered by the poorly studied mechanisms underlying PDIA1 expression regulation. Here, we showed that PDIA1 mRNA and protein levels were upregulated (average 5-fold) in the intima and media/adventitia following partial carotid ligation (PCL). Our search identified that miR-204-5p and miR-211-5p (miR-204/211), two broadly conserved miRNAs, share PDIA1 as a potential target. MiR-204/211 were downregulated in vascular layers following PCL. In isolated endothelial cells, gain-of-function experiments of miR-204 with miR mimic decreased PDIA1 mRNA while having negligible effects in markers of endothelial activation/stress response. Similar effects were observed in vascular smooth muscle cells (VSMC). Furthermore, PDIA1 downregulation by miR-204 decreased levels of the VSMC contractile differentiation markers. In addition, PDIA1 overexpression prevented VSMC dedifferentiation by miR-204. Collectively, we report a new mechanism for PDIA1 regulation through miR-204, and identify its relevance in a model of vascular disease playing a role in VSMC differentiation. This mechanism may be regulated in distinct stages of atherosclerosis and provide a potential therapeutic target.